Hubungan Ansietas dan Depresi dengan Fatigue pada Pasien Kanker yang Menjalani Kemoterapi - Ulfa Husnul Fata (Journal of Ners and Midwifery, 2015)
Fatigue is a symtoms that often arise in cancer patients undergoing chemotherapy. The purpose of this study was to determine the correlation between anxiety and depression with fatigue in cancer patients undergoing chemotherapy. Method: Research design was analytic with cross sectional approach. Research sample was 95 cancer patients undergoing chemotherapy in Dharmais Cancer Hospital Jakarta on November 7th to 28th, 2013, its choosed with consecutive sampling. Analysis using the Wilcoxon Signed Rank Test with significance p = 0,05. Result: The result showed that association between anxiety and fatigue with ï¡ = 0,005 and correlation coefficient 0,286, and association between depression and fatigue with ï¡ = 0,034 with correlation coefficient 0,218. Discussion: Anxiety and depression associated with fatigue in cancer patient undergoing chemotherapy, therefore, shoukd be taken to cope with anxiety and depression to prevent or decrease the incidence of fatigue in cancer patients undergoing chemotherapy.